Overcoming scarcity: how local innovations are transforming Western Kenya’s agricultural landscapes - Zemadim, Birhanu; Mwangi, O.; Adamtey, Noah; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
Across much of Kenya, periods of excessive rainfall are frequently followed by prolonged dry spells, with intermittent water scarcity largely driven by unmanaged variability in rainfall. Limited water management options significantly constrain food production and undermine resilience-building efforts. In this context, water harvesting and conservation innovations have become central to climate adaptation and the sustainability of rainfed farming systems. Locally driven water management practices enhance soil moisture retention, increase water availability, and reduce land degradation. In Agoro village, communities raised concerns about recurrent flooding, severe soil erosion from adjacent upland catchments, and persistent dry-season water shortages that negatively affected agricultural productivity and livelihoods. Through the CGIAR Research Program on Nature-Based Solutions (Nature+) and subsequently the Multifunctional Landscape Science Program, IWMI—working with local and international partners—undertook a comprehensive field investigation at the Agro-West aggregated farm in Kisumu County, western Kenya. The assessment combined transect walks, household surveys, GIS mapping, and geophysical surveys to identify flow paths, water accumulation zones, suitable infrastructure sites, and aquifer recharge potential. Infrastructure development commenced in October 2024 and was completed in June 2025. On a 76-hectare farm, concrete-lined drainage channels, water storage facilities, and a solar-powered irrigation system were constructed. These interventions improved water access, reduced flooding risks, enhanced water-use efficiency, and strengthened community resilience.